Toward an integrated ethical review process: an animal-centered research framework for the refinement of research procedures - Nannoni, Eleonora; Mancini, Clara (Frontiers in Veterinary Science, 2024)
The involvement of animals in research procedures that can harm them and to which they are deemed unable to consent raises fundamental ethical dilemmas. While current ethical review processes emphasize the application of the 3Rs (Replacement, Reduction and Refinement), grounded in a human-centered utilitarian ethical approach, a comprehensive ethical review also involves a harm-benefit analysis and the consideration of wider ethical issues. Nevertheless, to our knowledge, approaches are still needed to facilitate the integrative assessment and iterative revision of research designs to improve their ethical value or to identify cases in which using animals is irremediably unethical. Additionally, frameworks are lacking to explicitly include an animal-centered perspective into the ethical review process beyond welfare concerns, covering broader ethical considerations (such as consent). In previous work we proposed an Animal-Centered Research framework (ACRf) comprising four animal-centered research principles (relevance, impartiality, welfare and consent) which could help researchers and ethical review bodies apprise research designs from an animal-centered perspective. This paper builds on and further develops our previous work by contextualizing the ACRf within the bigger picture of animal research ethical review and by illustrating how their ACRf could be operationalized within current ethical review processes. This paper contributes an extended framework that integrates the application of the ACRf principles within the ethical review process. To this end, we present findings from a theoretical case study focusing on the ethical review of a research protocol on the study of stress response in pigs. We discuss how our extended framework could be easily applied to facilitate a holistic approach to the ethical review process, and inform an iterative process of refinement, to support the development of research designs that are both more ethical and scientifically valid.